(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Ethnic culture expresses its linguistic and cultural identity of the ethnic group, including the specific features of the material and spiritual culture, life, group psychological characteristics common identity based on the idea of their common origin. Ethnic culture, in addition, includes the language of the world of communication, which represents emerging in communications of various ethnic groups shared «communicative and cultural zones» – areas of global culture. In the culture of the ethnic group and the ethnic specific common worldwide languages coexist as represent different cultural layers. Based on the above, ethnic and cultural identity can be determined as part of a multiple identity which is a socio-cultural construct, transmit awareness of the individual himself as a member of an ethnic group, the degree of mastery of the ethnic culture and language, the adoption of its values and unconditional adherence to them in practice. Becoming the global cultural space and the emergence of a global culture occurs on the basis of cultural values that are common to all the world’s cultures. Although these values were in all cultures have always, however, the formation of a global culture of today occurs only during the information globalization of the world, when activated by the process of cultural interchange, leading to a deepening of the cultural self-development and enrichment at the expense of the development of a cultural experience. Therefore, in today’s world issues of national identity and national in¬teresa in the context of globalization are the focus of both researchers and policy makers. The global transformation of modern humanity at the turn of the century characterized voz¬niknoveniem new guidelines, new values. Relevant ideas become new world of the global economy, the integration of cultures, etc. The stronger the processes of globalization penetrate into the national culture, the more the nations are trying to protect the internal components such as culture, traditions, language and religion. That is, in the period of global transformations aggravated the problem of national identity related to people’s desire for identity and self-determination in the real world, and sohra¬nit defend their identity.